An in vitro cascade with four enzymes for the production of d-3, 4-dihydroxybutyric acid from d-xylose. Issue 19 (12th September 2022) - Zhang, Yipeng; Ma, Liting; Sun, Weikang; Xiao, Dan; Lü, Chuanjuan; Wang, Qian; Xu, Ping; Ma, Cuiqing; Gao, Chao
Abstract : Production of d -3, 4-dihydroxybutyric acid by using an NAD + and ATP free in vitro cascade with four enzymes from d -xylose, the predominant sugar in hemicellulosic biomass. Abstract : d -3, 4-Dihydroxybutyric acid (d -3, 4-DHBA) is an important platform chemical with diverse applications in the chemical and pharmaceutical industry. The reported metabolic pathway for d -3, 4-DHBA production from d -xylose involves two NAD-dependent dehydrogenase-catalyzed reactions and thus is redox-imbalanced. In this study, the mutant alditol oxidase from Streptomyces coelicolor A3 (ScAldO) was identified to catalyze the oxidation of d -xylose and d -3, 4-dihydroxybutanal, the two NAD-dependent dehydrogenase-catalyzed reactions required for d -3, 4-DHBA production. Then, an in vitro enzymatic cascade composed of ScAldO, dihydroxy acid dehydratase from Paralcaligenes ureilyticus, α-ketoacid decarboxylase from Lactococcus lactis and catalase from Aspergillus niger was constructed for the production of d -3, 4-DHBA from d -xylose. Under the optimal conditions, d -3, 4-DHBA at a concentration of 4.55 g L −1 was produced from d -xylose with a molar yield of 83% and a productivity of 0.217 g L −1 h −1 . The in vitro enzymatic cascade only requires four enzymes and excludes expensive cofactor addition and thus may be a potential choice for industrial biomanufacturing of d -3, 4-DHBA.